Kansas Fertilizer Research 2021 (Kansas Agricultural Experiment Station Research Reports, 2021)
A summary of research conducted in 2018-2020 on fertilizer use and management practices for crops in Kansas. Published in 2021 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Servicehttps://www.ag.k-state.edu/
Keywords: fertilizer; tillage; nitrogen; phosphorus; irrigation; sorghum; wheat; sulfur; corn; soybean; Kansas fertilizer; side-dress application; wheat protein content; endophyte-free tall fescue; claypan soil; subsurface drip irrigation